2016
DOI: 10.1080/09593330.2016.1150349
|View full text |Cite
|
Sign up to set email alerts
|

Purification and detoxification of petroleum refinery wastewater by electrocoagulation process

Abstract: The treatment of synthetic oily wastewater having the characteristics of a typical petroleum refinery wastewater (PRW) by electrocoagulation (EC) using iron and aluminum electrodes was conducted in an electrolytic reactor equipped with fluid recirculation. During the treatment, the emulsion stability was followed by the measurement of Zeta potential and particle sizes. Effects of some operating conditions such as electrodes material, current density and electrolysis time on removal efficiencies of turbidity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Recently, adsorption and electrocoagulation emerged as very effective solutions to overcome the major drawbacks of conventional processes in removing unwanted wastewater effluents (Hamdan and El-Naas 2014). These methods have the ability to remove a wide range of pollutants (Barrera-Díaz et al 2014;Elabbas et al 2016), such as phenolic wastes (Adhoum and Monser 2004), petroleum refinery wastewater (Gousmi et al 2016), organic wastewater (Mahvi et al 2011) ammoniac and phosphate treatment wastewater (Adebayo et al 2015), textile wastewater (Saeed et al 2015), and removal of heavy metals (Umran and Sadettin 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, adsorption and electrocoagulation emerged as very effective solutions to overcome the major drawbacks of conventional processes in removing unwanted wastewater effluents (Hamdan and El-Naas 2014). These methods have the ability to remove a wide range of pollutants (Barrera-Díaz et al 2014;Elabbas et al 2016), such as phenolic wastes (Adhoum and Monser 2004), petroleum refinery wastewater (Gousmi et al 2016), organic wastewater (Mahvi et al 2011) ammoniac and phosphate treatment wastewater (Adebayo et al 2015), textile wastewater (Saeed et al 2015), and removal of heavy metals (Umran and Sadettin 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, animals can be contaminated, and this contamination can reach human beings through the food chain. Previous works showed that hydrocarbon effluents were successfully treated by electrocoagulation [10,37,38]. However, to the best of our knowledge no dedicated work to electrocoagulation of oily effluents in sub-Saharian Africa was found, from where the choice to apply this process to the treatment of oily effluents of this company.…”
Section: Introductionmentioning
confidence: 94%
“…In EC experiments one of the important factors that determine the efficiency of the process is the type and combinations of electrodes. The type of materials that are used most often for EC experiments are Aluminum (Al) and iron (Stainless Steel (SS)) which are quite cheap (Gousmi et al 2016). In this work two types of electrode combinations have been used (Anode/Cathode): Al/SS, Mild Steel/SS.…”
Section: Changing Electrode Materialsmentioning
confidence: 99%